Inequality, Structure of Production and International Trade - The Role of Credit Market Imperfection - Hamid Beladi; Sugata Marjit; Suryaprakash Misra (Center for Economic Studies and ifo Institute (CESifo), 2017)
Credit rationing in the presence of asset inequality affects production and trade pattern in this paper, but not in the conventional way. A Ricardian general equilibrium framework with heterogeneous levels of asset ownership is developed to show that more equal asset distribution may contract the output of the credit intensive sector as redistribution to the bottom of the ladder fails to promote entrepreneurs. However, the same in favor of the middle of the ladder may do the opposite. We point out the possibility that an economy with relatively equal distribution of asset ownership may import capital or credit intensive good and also export capital, unlike in a conventional HOS model.
Keywords: F12; 330; credit; inequality; egalitarian distribution; trade